2020
DOI: 10.2147/cmar.s232708
|View full text |Cite
|
Sign up to set email alerts
|

<p>Research Progress Evaluating the Function and Mechanism of Anti-Tumor Peptides</p>

Abstract: Malignant tumors cause a high mortality rate worldwide, and they severely threaten human health and negatively affect the economy. Despite the advancements in tumor-related molecular genetics and effective new processes in anti-tumor drug development, the anti-tumor drugs currently used in clinical practice are inadequate due to their poor efficacy or severe side effects. Therefore, developing new safe and efficient drugs is a top priority for curing cancer. The peptide has become a suitable agent due to its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…Then we found that the activation of a variety of proteins depends on proteolytic processes. As a product of the proteolytic products, endogenous peptides can also directly interact with target cells or target proteins and thus regulate the targets' function (2). Indeed, most of the peptides' function was closely related with their precursor proteins (2).…”
Section: Gene Ontology and Pathway Analysis Of The Precursor Proteins Of The Differentially Expressed Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Then we found that the activation of a variety of proteins depends on proteolytic processes. As a product of the proteolytic products, endogenous peptides can also directly interact with target cells or target proteins and thus regulate the targets' function (2). Indeed, most of the peptides' function was closely related with their precursor proteins (2).…”
Section: Gene Ontology and Pathway Analysis Of The Precursor Proteins Of The Differentially Expressed Peptidesmentioning
confidence: 99%
“…As a product of the proteolytic products, endogenous peptides can also directly interact with target cells or target proteins and thus regulate the targets' function (2). Indeed, most of the peptides' function was closely related with their precursor proteins (2). So gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of the precursor proteins of the differentially expressed peptides were performed.…”
Section: Gene Ontology and Pathway Analysis Of The Precursor Proteins Of The Differentially Expressed Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…As of November 2019, more than 20 ACPs have been approved by FDA and EMA. ACPs like Kyprolis, SomaKit TOC, Lutathera and Gallium Dotatoc Ga68 have been marketed in recent years [ 16 ]. Collectively, ACPs represent a promising alternative to conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with the merits of relatively high tissue penetration and low occurrence of drug resistance, the clinical application prospect of ACPs are promising. A search of the US National Institutes of Health Clinical Trials database (https://clinicaltrials.gov/) using the phrase 'anti-cancer peptides' found 1002 peptide-based clinical trials that targeted different types of cancer [16]. For example, Bryostatin 1, one of the most abundant and best-studied peptides of the bryostatin family, has shown anti-tumour activity in Phase I trials in patients with malignant melanoma, lymphoma and ovarian carcinoma [17,18].…”
Section: Introductionmentioning
confidence: 99%